Menelusuri Jejak Pengetahuan Lokal Picung: Tradisi Kotok Bongkok sebagai Warisan Budaya Takbenda di Kabupaten Lebak - Dc Aryadi; Badrul Munir; Samsu Bahri; Usmaedi Usmaedi (Program Studi Pendidikan Sejarah, Universitas Setiabudhi Rangkasbitung, 2026)
This study aims to examine the traditional processing of picung fruit (Pangium edule) and a local food product known as kotok bongkok as part of the cultural heritage of the people of Lebak Regency, Banten. Picung is a distinctive food ingredient of the Indonesian archipelago that possesses a unique characteristic: in its raw state it contains toxic compounds in the form of hydrogen cyanide (HCN), yet through traditional processing it can be transformed into a safe culinary seasoning with high gastronomic value. This research employs a qualitative approach using an ethnographic method, involving field observations, in-depth interviews, and documentation of picung processing practices within the community. The findings indicate that the processing of picung involves several important stages, including fruit selection, boiling, peeling, soaking in flowing river water, natural fermentation, and final maturation before being used as a cooking ingredient. These processes not only function to eliminate toxic substances but also shape the distinctive color, aroma, and flavor that characterize local culinary traditions. Furthermore, picung also carries symbolic meaning within Sundanese culture, reflecting values of patience, life processes, and the harmonious relationship between humans and nature. Therefore, the tradition of processing picung and producing kotok bongkok can be understood as a form of local knowledge that is important to document. This study emphasizes the urgency of inventorying this tradition as part of the intangible cultural heritage of Lebak Regency in order to preserve the continuity of local knowledge and strengthen the cultural identity of the community in the midst of ongoing social change.